HYROLOGICAL RELATIONSHIP BETWEEN SURFACE AND GROUNDWATER IN BADRA - JASSAN BASIN - Al-Shamaa, Issar; Ali, Batool (Iraqi Journal of Science, 2024)
Surface and Groundwater's has an associated hydrological relationship affected bydeferent factors related to Geological, Hydrological and Climatic conditions where thesefactors control the circumstances of groundwater movement in shallow aquifers as wellas the quantity of water can be gained or lost from the aquifer and river. In Badra -Jassan basin, the main River is Galal Badra which flows from inside Iranian territorywith two tributaries and discharge water in Al- Shuacha marshes to the south , most ofriver water depends on water gained from inside Iranian territory. Part of thegroundwater discharge to the river basin in specific areas according to the topography of the river valley as well as height of groundwater level in the shallow aquifer above thesurface water in the river. At the same time the shallow aquifer which consist of layersand deposits of gravel, sand and silt gained water from river in certain locations, wheregroundwater quality has changed according to levels of Natural Nutrition to be similar tochemical quality of surface water in those sites. Recharge and discharge levels ofgroundwater within the river has determined by drawing a hydrogeological section alongthe river and study of the hydrochemical characteristics of groundwater and surfacewater in the basin.